1984
DOI: 10.1073/pnas.81.4.1122
|View full text |Cite
|
Sign up to set email alerts
|

Denervated skeletal muscle displays discoordinate regulation for the synthesis of several myofibrillar proteins.

Abstract: Synthesis patterns of myosin heavy-and light-chain isoforms, tropomyosin and troponin, have been studied in chicken fast muscle denervated at both neonatal and adult stages. Denervated neonatal muscle does not synthesize the adult myosin heavy-chain isoform at the time of denervation, but it does synthesize the adult isoform several months after denervation. Thus, innervation does not appear to be necessary for the normal sequential replacement of embryonic and neonatal myosin heavy chain by the adult variant.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 36 publications
2
24
0
1
Order By: Relevance
“…This suggests a potential role for innervation in regulation of MHC isoform protein expression. However, previous studies have suggested that innervation is not a requirement for the ultimate expression of adult fast MHC protein isoforms (6,8,27,32). Furthermore, during postnatal development of the rat Dia m , removal of innervation with unilateral denervation only delayed expression of fast MHC protein isoforms and prolonged expression of the MHC Neo protein isoform (39).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a potential role for innervation in regulation of MHC isoform protein expression. However, previous studies have suggested that innervation is not a requirement for the ultimate expression of adult fast MHC protein isoforms (6,8,27,32). Furthermore, during postnatal development of the rat Dia m , removal of innervation with unilateral denervation only delayed expression of fast MHC protein isoforms and prolonged expression of the MHC Neo protein isoform (39).…”
Section: Discussionmentioning
confidence: 99%
“…Sur le plan métabolique, on observe, après dénervation, une diminution de la synthèse et une augmentation de la dégradation de la majeure partie des protéines intracellulaires (Padieu, 1959 ;Schapira et Dreyfus, 1959 ;Gutmann, 1962 (Gauthier et Carraro etal., 1985), tropomyosine, troponine et chaînes légères de la myosine évoluent vers des configurations embryonnaires (Dhoot et Perry, 1982 ;Matsuda et al, 1984a ;Obinata et al, 1984 ;Shimizu et Shimada, 1985).…”
Section: A) Propriétés Des Fibres Musculairesunclassified
“…MHC isoform transitions have also been described during myogenesis in mouse (Weydert et al, 1983(Weydert et al, , 1987 and chicken (Bandman et al, 1982). Developing avian muscles exhibit isoform transitions in the MLCl gene family (Barton et al, 1988), the actin gene family (Hayward and Schwartz, 1986), and the tropomyosin (Tm) and troponin T (TnT) gene families (Matsuda et al, 1981(Matsuda et al, , 1984. Similarly, in mammals, embryonic isoform profiles differ from those of adult skeletal muscles for MLCl (Periasamy et al, 1984;Barton et al, 1988Barton et al, , 1989Lyons et al, 1990), actin (Buckingham, 1985), and TnT (Briggs et al, 1990;Saggin et al, 1990).…”
Section: Introductionmentioning
confidence: 99%